Dampak Bencana Alam Terhadap Inflasi di Indonesia - Nuranisa; Doni Satria (Universitas Negeri Padang, 2025)
This research aims to determine and analyze the impact of natural disasters on inflation in Indonesia. This research uses secondary data from the National Disaster Management Agency (BNPB) and the Central Statistics Agency (BPS), in the form of panel data in 32 provinces in Indonesia. The dependent variable in this research is the inflation rate in each province in Indonesia. The independent variables of this research are the frequency of disasters, the level of damage due to disasters, and supply disruptions. As control variables, this research uses Realized Provincial Government Expenditures and Gross Regional Domestic Product (GRDP) Per Capita. This research analysis method uses panel data with a Random Effect Model (REM) approach. The main focus in this research is hydrometeorological disasters, because this type of disaster dominates natural disasters in Indonesia during the research period. The research results concluded that the frequency of disasters in the previous year (disaster frequency lag) had a significant effect on inflation in Indonesia. According to the types of disasters, only flood disasters have a positive and significant effect on inflation in Indonesia. Keywords : Inflation, Supply Disruptions, Disaster Frequency, APBD, GRDP Per Capita